GROWTH OF ECOGEOLOGICAL STRESSES IN MOUNTAINOUS GEOSYSTEMS IN THE CONDITIONS OF ACTIVATION MODERN DANGEROUS GEOMORPHODINAMICPROCESSES (on the example of Azerbaijan) - Tarikhazer Stara Abulfasgizi (Scientific Journal of Pedagogy and Economics, 2019)
The questions of negative influence of modern dangerous geomorphodinamicprocesses (MDGP) within the limits of the Azerbaijan are considered in the article. With the purpose of definition of a degree of influence of modern dangerous geomorphodinamicprocesses to the human and on an economic infrastructure the classification of territory by a degree of ecogeomorphological dangers and division into districts of ecogeomorphological areas was carried out.To evaluate the structure of modern dangerous geomorphodynamic processes we used the method of expert and statistical estimates of the area of propagation (intensity) of a process in geoecological region.Аnalysis of modern dangerous geomorphodynamic processes within ecogeomorphological regions of Azerbaijan, mountain geosystems that have been actively developed in the recent years for development of mountain tourism, agriculture, etc. allows us to conclude that in this region the most dangerous processes are earthquakes, landslides, mud flows, caving, sheet and river erosion, etc. They create overall ecodynamically stressed situation that requires to conduct advanced consistent, large scale expert evaluation of ecogeomorphological situation within the boundaries of each mountain ecosystem prior to its large-scale development for mitigations of the threats for human activities. The results obtained during the assessment of the effect of natural and man-caused factors on the stability of montane ecosystems may be used to forecast dangerous natural phenomena and to research geodynamical dangerous geomorphodinamic process not only in Azerbaijan, but also in other regions of the Alpine-Himalayan orogenic belt.